2019
DOI: 10.5222/mmj.2019.25986
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Nasal Septum Angulation and Its Association with Rhinosinusitis Symptom Scores

Abstract: The aim of the study was to determine the association of angulation of nasal septum with the severity of rhinosinusitis as measured by symptom score and Visual Analog Score (VAS). Method: The study was performed as a cross sectional study conducted at two different centres in Malaysia. Ninety-eight patients who were diagnosed with rhinosinusitis and fulfilled the selection criteria were assessed as for the symptom score and VAS and the measurement of angulation of nasal septum was performed through a coronal v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…Sinusitis frequency and sinus score from CT scan resultsSinusitis Frequency (n) Percentage (%)Lazim NM et al (2019) reported that the severity of nasal septal deviation angulation was significantly related to the degree of severity of CRS based on symptom scores and VAS [25]. Poorey and Gupta (2014) reported 67 CT scans of patients with CRS which were 56.7% had a degree of septal deviation moderate and were correlation between the degree of deviation of the nasal septum and changes in the maxillary sinus mucosa (p <0.05), but did not correlate with changes in the mucosa of the ethmoidal, frontal and sphenoidal sinuses [26].…”
mentioning
confidence: 99%
“…Sinusitis frequency and sinus score from CT scan resultsSinusitis Frequency (n) Percentage (%)Lazim NM et al (2019) reported that the severity of nasal septal deviation angulation was significantly related to the degree of severity of CRS based on symptom scores and VAS [25]. Poorey and Gupta (2014) reported 67 CT scans of patients with CRS which were 56.7% had a degree of septal deviation moderate and were correlation between the degree of deviation of the nasal septum and changes in the maxillary sinus mucosa (p <0.05), but did not correlate with changes in the mucosa of the ethmoidal, frontal and sphenoidal sinuses [26].…”
mentioning
confidence: 99%